К исследованию механизма термобрикетирования торфа - Маслов С. Г. Станислав Григорьевич; Смольянинов С. И. Станислав Иванович; Смольянинова Н. М.; Ощепков И. А. (1971, 1971)
Заглавие с титульного листа